2002
DOI: 10.1007/s003300200003
|View full text |Cite
|
Sign up to set email alerts
|

Multidetector-row CT cardiac imaging with 4 and 16 slices for coronary CTA and imaging of atherosclerotic plaques

Abstract: IntroductionDespite a multitude of different medical and interventional strategies to treat coronary artery disease (CAD), the natural course of CAD is a relentless progression. The current gold standard to assess the degree of stenosis is coronary angiography. In Germany alone, the total number of angiographic procedures rose by 45% from 1995 to 2000, while the fraction of interventional procedures remained almost constantly low at about 30% [1]. Although coronary angiography has become a safe procedure with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
2

Year Published

2003
2003
2009
2009

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 28 publications
0
20
0
2
Order By: Relevance
“…On first patient scans we demonstrated significantly improved visualization of calcified and noncalcified plaques and of stents owing to submillimeter slice width and optimized in-plane resolution. Meanwhile, clinical experience has shown the potential of 16-slice technology for cardiac imaging [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…On first patient scans we demonstrated significantly improved visualization of calcified and noncalcified plaques and of stents owing to submillimeter slice width and optimized in-plane resolution. Meanwhile, clinical experience has shown the potential of 16-slice technology for cardiac imaging [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…The arrow shows the non-assessable segment This generation of scanner offers the simultaneous acquisition of 16 slices with sub-millimeter collimation, e.g., 0.75 mm. The breath-hold time decreases to less than 20 s, and the voxel becomes truly isotropic with a spatial resolution of 0.5×0.5×0.6 mm [5,13]. With this technique, Ropers could assess 88% of coronary arteries with a diameter of at least 1.5 mm in a group of 77 patients [14].…”
Section: Figmentioning
confidence: 97%
“…Initial studies reported sensitivity and specificity rates of 59% to 95% and 79% to 98%, respectively, primarily in patients with stable angina pectoris referred for cardiac catheterization ( Table 1). The rate of adequate visualization of coronary vessels in these studies ranged from 68% to 96% [18][19][20][21][22][23][24][25][26][27][28]. These results have compared favorably with other modalities such as intravascular ultrasound and cardiac magnetic resonance imaging [29,30] but are still inadequate.…”
Section: Technical Aspects Of Ct/mdctmentioning
confidence: 93%